GroEL from the endosymbiont Buchnera aphidicola betrays the aphid by triggering plant defense - Chaudhary, Ritu (National Academy of Sciences, 2014)
Aphids are sap-feeding plant pests and harbor the endosymbiont Buchnera aphidicola, which is essential for their fecundity and survival. During plant penetration and feeding, aphids secrete saliva that contains proteins predicted to alter plant defenses and metabolism. Plants recognize microbe-associated molecular patterns and induce pattern-triggered immunity (PTI). No aphid-associated molecular pattern has yet been identified. By mass spectrometry, we identified in saliva from potato aphids (Macrosiphum euphorbiae) 105 proteins, some of which originated from Buchnera, including the chaperonin GroEL. Because GroEL is a widely conserved bacterial protein with an essential function, we tested its role in PTI. Applying or infiltrating GroEL onto Arabidopsis (Arabidopsis thaliana) leaves induced oxidative burst and expression of PTI early marker genes. These GroEL-induced defense responses required the known coreceptor BRASSINOSTEROID INSENSITIVE 1-ASSOCIATED RECEPTOR KINASE 1. In addition, in transgenic Arabidopsis plants, inducible expression of groEL activated PTI marker gene expression. Moreover, Arabidopsis plants expressing groEL displayed reduced fecundity of the green peach aphid (Myzus persicae), indicating enhanced resistance against aphids. Furthermore, delivery of GroEL into tomato (Solanum lycopersicum) or Arabidopsis through Pseudomonas fluorescens, engineered to express the type III secretion system, also reduced potato aphid and green peach aphid fecundity, respectively. Collectively our data indicate that GroEL is a molecular pattern that triggers PTI.